Warrantless arrest laws for domestic violence: How are youth affected? - Kabir Dasgupta; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2016)
This study empirically examines the impact of warrantless arrest laws (designed to deter domestic violence) on multiple youth outcomes. Utilizing variation in the timing of implementation of the laws, and employing a difference in differences framework, we examine both the direct and indirect impacts on youth in the United States. There appears to be no significant direct link between warrantless arrest laws and domestic violence-related homicides. However, on the indirect front, we do find strong evidence that implementation of the arrest laws result in a drop in the probability of youth experiencing suicidal ideation, and some evidence pointing to a drop in their likelihood of engaging in substance use behaviour. This analysis also accounts for important heterogeneities in laws across states, and our findings are robust to multiple sensitivity checks, aimed at addressing key threats to identification.
Keywords: I12; K36; 330; Domestic violence; Warrantless arrest laws; Homicide; Youth; Mental health; Difference-in-differences